Metode Eigenface Dalam Presensi Siswa/i Pada SMK Saentis Berbasis Android - Silitonga, Josua Endrico H (U-NET Jurnal Teknik Informatika, 2023)
SMK Saentis is an institution engaged in the world of education. However, there are obstacles encountered in the student attendance system, which is still running with a manual attendance system, where students fill in attendance for each subject by providing information or initials students have attended and participated in the teaching and learning process. This is certainly less effective because it opens up opportunities to commit fraud. In addition, the recapitulation is done manually which takes a long time because it has to enter a lot of data. This attendance attendance has an effect on the student attendance assessment process so that it takes a long time to make student attendance reports. Therefore, the authenticity of student attendance data is needed so that the assessment process can run well. To overcome these problems, a student attendance attendance application system is needed to obtain accurate attendance results. By designing an android-based facial attendance application system and using the Eigenface method to overcome these problems. So that the attendance process can be done more accurately and can overcome cheating attendance from students. In the system that will be designed, students are required to take attendance through the camera process on the Smartphone by standing in front of the camera sensor and being able to recognize a person's face even though the person does not directly carry out the attendance process. Then from the results of this facial recognition, it is used to update the presence status of a person in a place or room.